Performance Indicators of Sheep Fed Rice Straw Supplemented with Browse Leaves - Adogla-Bessa, T.; Sarkwa, F.O.; Adjorlolo, L.K.; et al. (African Journal of Food, Agriculture, Nutrition and Development, 2022)
The use of browse leaves as a protein source can help ruminants cope with adverse nutritional stress under unpredictable climatic conditions. The objective of this study was to determine feed intake, digestibility, metabolisable energy intake, weight gain and feed conversion efficiency of sheep fed untreated rice straw supplemented with browse leaves. Four forest type rams with an average weight of 27.75± 0.89 kg (2 years old) and in a replicated 4 x 4 Latin square design were used in the digestibility study. Twelve ram lambs of average weight 13.2 kg ± 0.05 kg were assigned to the experimental diets randomly for 12 weeks in the growth study in a completely randomized design. Animals were fed four diets namely: Untreated rice straw (URS) + Albizzia lebbek (AL) (Control), URS + Moringa oleifera (MO), URS + Ficus exasperata (FE) and URS + Spondias mombin (SM). The dietary treatment influenced (p<0.05) the digestible organic matter in dry matter (DOMD), maintenance energy requirement (MEm), metabolisable energy intake (MEI) and ratio of metabolisable energy intake to maintenance energy requirement (MEI: MEm). The DOMD, MEm, MEI and MEI: MEm were in the range of 965-983 g/kgDM, 3.61-5.36 MJ/d, 9.51-15.8 MJ/d and 2.63-3.38 respectively. The total intake of browse and straw ranged from 428.71 to 487.14 g/d. The average daily gain ranged from 7.14 to 20.24 g/d. The animals fed URS+FE recorded the highest average daily gain (p<0.05) while the animals fed URS+AL recorded the lowest average daily gain (p<0.05). Feed conversion efficiency ranged from 25.97 to 71.45 kg feed/ kg gain. The sheep fed URS+FE were the most efficient (p<0.05) and those fed URS+AL, the least efficient (p<0.05). Supplementation of browse leaves to sheep using untreated rice straw as a basal diet improved digestibility with moderate weight gains. These browse leaves (AL, FE, MO and SM) can be used to supplement poor quality ruminant diets for improved performance particularly during periods of feed scarcity. Key words: Digestible organic matter in dry matter, metabolisable energy, weight
Research Article
Keywords: Digestible organic matter in dry matter; metabolisable energy; weight gain